2015
DOI: 10.1186/s40545-015-0042-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, prescribing and barriers to effective management of hypertension in older populations: a narrative review

Abstract: ObjectivesHypertension is the leading modifiable cause of mortality worldwide. Unlike many conditions where limited evidence exists for management of older individuals, multiple large, robust trials have provided a solid evidence-base regarding the management of hypertension in older adults. Understanding the impact of age on how the prevalence of hypertension and the role of pharmacotherapy in managing hypertension among older persons is a critical element is the provision of optimal health care for older pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 73 publications
0
3
0
1
Order By: Relevance
“…Several barriers to the optimal management of hypertension among older adults have been identified and tend to be system‐, physician‐ and patient‐related, such as uncertainty around the applicability of management guidelines for older persons and patient adherence to treatment for a largely asymptomatic condition 22 . This is despite the fact that treatment of hypertension in the elderly has been associated with a decrease in cardiovascular morbidity and mortality 8 …”
Section: Discussionmentioning
confidence: 99%
“…Several barriers to the optimal management of hypertension among older adults have been identified and tend to be system‐, physician‐ and patient‐related, such as uncertainty around the applicability of management guidelines for older persons and patient adherence to treatment for a largely asymptomatic condition 22 . This is despite the fact that treatment of hypertension in the elderly has been associated with a decrease in cardiovascular morbidity and mortality 8 …”
Section: Discussionmentioning
confidence: 99%
“…Pandeminin başlarında gerek virüsün ACE2 kullanması gerekse HT olan hastalarda, hastalığın daha ölümcül seyretmesi özellikle anjiyotensin 1 reseptörü (AT1r) blokajı üzerinden etki eden anti-HT ilaçların suçlanmasına neden olmuştur. Unutulmamalıdır t ki COVID-19 hastalarında en yüksek mortalite ve morbidite 65 yaş üzerinde (%84) olmakta, fakat bu hasta grubunda HT ve KV risk prevelansının da benzer oranlarda olduğu görülmektedir (>60 yaş %65) (17). Bu nedenle COVID-19 hastalarında mortalite ve morbidite ile HT birlikteliğini araştırmak için eldeki veriler yeterli görünmemektedir.…”
Section: Covid-19 Ve Hipertansiyonunclassified
“…The prevalence of hypertension increases with age, and it is estimated that older adults over the age of 65 years account for 70% of all adult hypertension in developed countries (Logan, 2011, Pimenta and Oparil, 2012). While the prevalence of hypertension in older adults is high, there is robust evidence regarding the benefits of good blood pressure (BP) control within this population, in terms of reduced mortality and morbidity (Wing et al, 2003, Bulpitt et al, 2011, Dahlöf et al, 1991, Alhawassi et al, 2015). A recent Cochrane review examining 15 clinical trials looking specifically at pharmacotherapy for hypertension in older patients found that treating those aged 60 years or older with mild to moderate hypertension reduced both all cause mortality and cardiovascular morbidity and mortality in older people (Musini et al, 2009).…”
Section: Introductionmentioning
confidence: 99%